Solutions of the Force-Free Duffing-van der Pol Oscillator Equation. (26th October 2011) - Khan, Najeeb Alam; Jamil, Muhammad; Ali, Syed Anwar; Khan, Nadeem Alam
Abstract : A new approximate method for solving the nonlinear Duffing-van der pol oscillator equation is proposed. The proposed scheme depends only on the two components of homotopy series, the Laplace transformation and, the Padé approximants. The proposed method introduces an alternative framework designed to overcome the difficulty of capturing the behavior of the solution and give a good approximation to the solution for a large time. The Runge-Kutta algorithm was used to solve the governing equation via numerical solution. Finally, to demonstrate the validity of the proposed method, the response of the oscillator, which was obtained from approximate solution, has been shown graphically and compared with that of numerical solution.